2021
DOI: 10.1111/1541-4337.12790
|View full text |Cite
|
Sign up to set email alerts
|

Food‐grade carrageenans and their implications in health and disease

Abstract: Food additives, often used to guarantee the texture, shelf‐life, taste, and appearance of processed foods, have gained widespread attention due to their increased link to the growing incidence of chronic diseases. As one of the most common additives, carrageenans have been used in human diets for hundreds of years. While classified as generally recognized as safe (GRAS) for human consumption, numerous studies since the 1980s have suggested that carrageenans, particularly those with random coil conformations, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 125 publications
(190 reference statements)
1
36
0
Order By: Relevance
“…K-carrageenan and ι-carrageenan are commonly used for tissue engineering-related applications. K-carrageenan forms thermally reversible brittle and stiff gels, while ι-carrageenan forms elastic and soft gels [8]. λ-carrageenan does not form hydrogels and is even more fluidic compared to the other carrageenan isoforms.…”
Section: Introductionmentioning
confidence: 96%
“…K-carrageenan and ι-carrageenan are commonly used for tissue engineering-related applications. K-carrageenan forms thermally reversible brittle and stiff gels, while ι-carrageenan forms elastic and soft gels [8]. λ-carrageenan does not form hydrogels and is even more fluidic compared to the other carrageenan isoforms.…”
Section: Introductionmentioning
confidence: 96%
“…However, other toxicological studies have found no evidence that CGNs may upregulate pro-inflammatory molecules and promote intestinal inflammation [ 14 ]. Of note, data on the safety of CGNs obtained in cell culture experiments should not be overinterpreted as CGN and its interaction in the gut with colonic microbiome are poorly understood [ 15 , 16 , 17 , 18 ]. Yet, this is of great importance due to recent reports on the ability of CGNs to magnify pathogen-induced inflammation in the intestine of mice [ 19 ], contribute to inflammatory bowel disease aggravation [ 20 , 21 ], and enhance lipopolysaccharide (LPS)-induced production of pro-inflammatory cytokines such as tumor necrosis factor-alpha (TNFα) and interleukin-8 (IL-8) [ 19 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…International regulatory authorities such as the U.S.-based Food and Drug Administration (FDA) and European Food Safety Authority (EFSA) have initiated the thoughtful reevaluation of food additives to guarantee their safety for consumers. Among the food additives whose safety is debated, carrageenans seem to be the most controversial [1][2][3][4][5]. Carrageenans are phycocolloids of heteropolysaccharide origin commercially produced from red algae and widely represented in human diet.…”
Section: Introductionmentioning
confidence: 99%
“…Cost-effectiveness and convenience of their application in technological processes make them indispensable in the production of processed and ultraprocessed food. The content of carrageenans, which are registered as native carrageenan (E407) and semi-refined form (E407a) can vary to a high extent and may reach 0.5-1% of weight for some dairy products, processed meat and fruit-based processed foods [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation